Do Women With Breast Cancer Who Choose Adjunctive Integrative Oncology Care Receive Different Standard Oncologic Treatment?. (September 2018) - Standish, Leanna J.; Dowd, Fred; Sweet, Erin; Dale, Linda; Andersen, M. Robyn
Purpose: To determine if women with breast cancer who choose adjunctive naturopathic oncology (NO) specialty care receive different standard oncologic treatment when compared with breast cancer patients who receive only standard care.Participants: Women with breast cancer stages 0 to 4, aged 18+ who spoke English and sought care from outpatient naturopathic doctor clinics were enrolled in an observational study of clinical and quality of life outcomes. Women who sought NO care 2 or more times within the first 2 years postdiagnosis were identified as NO cases. A matched comparison group of breast cancer patients were identified using the Western Washington Cancer Surveillance System(CSS).Methods: A longitudinal cohort design. In addition to self-report data, the CSS provided data on demographics, stage at the time of diagnosis, and initial treatment. Oncology medical records were abstracted in order to provide additional information on standard oncologic treatment for all participants.Results: Cohorts were well matched with regard to demographic, histologic, and prognostic indicators at the time of diagnosis. Approximately 70% of women in both cohorts received standard oncologic care that met the National Comprehensive Cancer Network guidelines. There were no statistically significant differences between the cohorts in treatment received. Fewer women in the NO cohort with estrogen receptor–positive breast cancer appear to have received antiestrogen therapy.Conclusions: Women in both cohorts appear to receive guideline-concordant care. However, women who receive adjunctive NO care may be less likely to receive antiestrogen therapy.